The Influence of Green Knowledge, Green Product, and Perceived Price on Repurchase Intention of Environmentally Friendly Plastic Products with Green Satisfaction as a Mediating Variable - Rudiyanto Rudiyanto; Yanti Puspa Rini (LPPM Universitas Buddhi Dharma, 2026)
Growing environmental concerns have encouraged the increasing use of environmentally friendly plastic products. However, achieving consistent repurchase behavior remains a challenge. This study examines the effects of Green Knowledge, Green Product, and Perceived Price on Repurchase Intention, with Green Satisfaction as a mediating variable. Using a quantitative survey approach, data were collected from 278 users of eco-friendly plastic products in the Jabodetabek area. The data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that Green Knowledge has a positive and significant effect on Repurchase Intention, but does not significantly influence Green Satisfaction. Green Product has a positive and significant effect on Green Satisfaction, yet shows a negative and significant effect on Repurchase Intention. Perceived Price positively and significantly affects both Green Satisfaction and Repurchase Intention. Furthermore, Green Satisfaction has a positive and significant effect on Repurchase Intention. The mediation analysis reveals that Green Satisfaction mediates the effects of Green Product and Perceived Price on Repurchase Intention, but fails to mediate the effect of Green Knowledge on Repurchase Intention. These findings suggest that consumer satisfaction with environmentally friendly products is driven more by product attributes and price perceptions than by environmental knowledge alone. This study provides theoretical implications for the development of sustainable consumer behavior and practical implications for businesses to prioritize product quality and competitive pricing strategies in order to enhance consumer satisfaction and repurchase intention.